Measurement and modeling of methane diffusion in hydrocarbon mixtures. (15th September 2022) - Shi, Zhuofan; Khodaparast, Pooya; Hu, Sheng; Tsotsis, Theodore; Jessen, Kristian
Highlights: CH4 diffusion in n-alkane mixtures was studied including effects of liquid swelling. Constant binary diffusivities can predict diffusion in multicomponent systems. Sigmund's correlation must be tuned separately for binary, ternary and quaternary mixtures. Abstract: Methane (CH4 ) dissolution and diffusive mass transfer in liquid hydrocarbon mixtures is of key interest in the context of enhanced oil recovery from tight shales. In this paper, we have studied CH4 dissolution and diffusion in normal alkane mixtures at a temperature of 50 ⁰C and at pressures of ∼8 MPa. For the measurement of CH4 dissolution/diffusion in bulk liquid hydrocarbon mixtures, we have utilized a high pressure and temperature, constant-volume diffusion (CV-D) setup. We have studied CH4 diffusion in mixtures with three long-chain normal alkanes: decane (C10 ), dodecane (C12 ) and hexadecane (C16 ). We have measured CH4 solubility and diffusion in its binary mixtures with each of these three normal alkanes, as well as in ternary and quaternary mixtures. During the experiments, the swelling of the liquid mixture due to CH4 dissolution was measured in situ via a cathetometer and was subsequently integrated into the data analysis. A key conclusion from this study is that the solubility and transport properties of the multicomponent mixtures can be predicted accurately from binary mixture measurements using an appropriate Equation of State (EOS) and Wilke's simplification of the classical Maxwell-Stefan (MS) diffusion theory. This observation can facilitate accurate prediction of diffusive mass transfer in more complex liquid hydrocarbon mixtures.